Preventive effect of fermented black ginseng against cisplatin-induced nephrotoxicity in rats - Jung, Kiwon; An, Jun Min; Eom, Dae-Woon; Kang, Ki Sung; Kim, Su-Nam (KOREAN SOC GINSENG, 2017)
Background: Fermented black ginseng (FBG) is processed ginseng by the repeated heat treatment and fermentation of raw ginseng. The protective effect and mechanism of FBG on cisplatin-induced nephrotoxicity was investigated to evaluate its therapeutic potential. Methods: The free radical scavenging activity of FBG was measured using 1,1-diphenyl-2-picrylhydrazyl (DPPH). In addition, the protective effect against cisplatin-induced renal damage was tested in rats. FBG was orally administered every day at a dose of 150 mg/kg body weight for 10 d, and a single dose of cisplatin was administered intraperitoneally (7.5 mg/kg body weight) with 0.9% saline on the 4th d. Results: The DPPH radical-scavenging activity of FBG (IC50 = 384 mu g/mL) was stronger than that of raw ginseng. The improved DPPH radical-scavenging activity was mediated by the generation phenolic compounds. The decreased cell viability by cisplatin was recovered significantly after treatment with FBG in a dose-dependent manner. Then, the protective effect of FBG on cisplatin-induced oxidative renal damage was investigated in rats. The decreased creatinine clearance levels, which are a reliable marker for renal dysfunction in cisplatin-treated rats, were reduced to the normal level after the administration of FBG. Moreover, FBG showed protective effects against cisplatin-induced oxidative renal damage in rats through the inhibition of NF-kappa B/p65, COX-2, and caspase-3 activation. Conclusion: These results collectively show that the therapeutic evidence for FBG ameliorates the nephrotoxicity via regulating oxidative stress, inflammation, and apoptosis. (C) 2017 The Korean Society of Ginseng, Published by Elsevier Korea LLC.
Keywords: DIABETIC RENAL DAMAGE; OXIDATIVE STRESS; PANAX-GINSENG; RED GINSENG; IN-VITRO; ANTIOXIDANT; APOPTOSIS; INCREASE; INFLAMMATION; MEDICINE